Construction of Sandwich‐Like r‐Fe3O4/rGO@CN Anode Materials as Conductive Agent‐Free Anode for Lithium‐Ion Batteries. Issue 1 (18th November 2022) - Zhou, Hui; Zhou, Ju; Wang, Jitong; Ling, Licheng; Qiao, Wenming
Abstract: Fe3 O4 is a prospective anode material but faces challenges to develop high‐performance electrodes for lithium‐ion battery. In this paper, Fe3 O4 nanorods wrapped with reduced graphene oxide (rGO) as the conducting matrix and an amorphous nitrogen‐doped carbon (CN) as the protective coating were prepared using the hydrothermal method and freeze‐drying process. The obtained Fe3 O4 nanorods are uniformly dispersed on the rGO nanosheet. The addition of rGO improves the electrical conductivity of the composite, while the amorphous carbon layer mitigates the volume expansion effect of Fe3 O4 nanorods. Moreover, the in‐situ nitrogen doping accelerates the wetting effect of the electrolyte as well as reduces the diffusion and transfer resistance. Therefore, the obtained r‐Fe3 O4 /rGO@CN composite as conductive agent‐free anode exhibits outstanding performance and cycling stability at suitable nitrogen‐doped carbon coverage. The capacity could be maintained at 1020.7 mA h g −1 after 100 cycles at a current density of 0.5 A g −1 . In addition, the capacity fading rate of per cycle is only 0.08% at a high current density of 2 A g −1 . Our findings suggest that the prepared r‐Fe3 O4 /rGO@CN composite is a prospective candidate for utilization as an anode material in lithium‐ion batteries. Abstract : Herein, a sandwich‐like r‐Fe3 O4 /rGO@CN composite was prepared by hydrothermal method, freeze‐drying technique and high adhesive property of dopamine. The structure exhibits excellent cycling stability at suitable nitrogen‐doped carbon coverage, and the capacity is maintained at 1020.7 mA h g −1 after 100 cycles at a current density of 0.5 A g −1, and at a high current density of 2 A g −1, the capacity fading rate per cycle is only 0.08 %.